Body Composition and Physical Fitness Analysis in Different Field Position U-15 Soccer Players - Espada, Mário (2020)
The individual characteristics related to anthropometry, body composition, and physical capacities are important in the performance of soccer players, especially in terms of field position, which isone of the aspects to be considered in talent identification. A total of 48 soccer players under15 years of agewere evaluated using a Tanita UM076scale (body composition), Ergojump system (lower limb strength), handgrip (maximum isometric strength of hand and forearm muscles), Illinois agility test (agility), 30-meter sprint test (speed), and sit and reach test (flexibility). IBM SPSS 24 was used for data analysis, namely, descriptive analysis, analysis of variance (one-way ANOVA)andTukey posteriori test (p < 0.05) to confirm significant differences regarding the soccer players different field positions factor.Pearson's correlation test (p < 0.01 and p < 0.05) was used to confirm the existence of correlations between variables. We observedstatistically significant differences between players from different field positions in terms of body composition and agility. Strong correlations were verifiedbetweenthe body composition variables, as well as between the variables of physical capacities and when analyzing body composition relationship to physical capacities. Our results point to the fact that soccer players of certain field positions present specific characteristics.This informationcan help coachesto optimize training tasks and performance enhancementsduringthe soccer game. In addition, these results canprovide support in the definition ofevaluation criteria for anthropomet